Implementation of village fund allocation in reducing stunting in children - Rini Noviyanti; Asnawi Abdullah; Marlizar Ali (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The effective allocation of village funds has become a strategic approach to addressing stunting in rural communities. By investing in health, nutrition, sanitation, and educational programs, villages aim to improve maternal and child health outcomes, increase community awareness, and reduce the prevalence of stunting among children. Purpose: To analyze the implementation of village fund allocation in reducing stunting rates Method: A descriptive qualitative approach, specifically focusing on exploratory study. The study took place December 2024 - January 2025, in Peudada District, Aceh. Using total sampling 2 participants were selected, contributor informant inquired head of the stunting locus and head stunting reduction acceleration team. Data collection was carried out using in-depth interviews. The data were analysed using thematic analysis technique. Results: Village Funds have been instrumental in reducing stunting through programs targeting sanitation, supplementary food (PMT), Posyandu activities, direct cash assistance (BLT), and early childhood education (PAUD). Monitoring and evaluation by cadres and village midwives through home visits have improved children’s nutritional status and access to sanitation. Village cadres and officials, supported by the Stunting Committee (Komting), coordinate planning, budgeting, supervision, and community collaboration. Despite challenges such as budget constraints, uneven facility access, and low participation, strengthening coordination, diversifying programs, and applying innovative education methods are essential for sustainable stunting reduction, emphasizing the synergy between health and education sectors. Conclusion: Village officials contribute through budget planning, supervising cadres, and forming stunting committees to increase participation. Programs such as supplementary feeding, sanitation improvements, house rehabilitation, and PAUD have effectively reduced stunting and improved community quality of life.